Frequency of Vitamin D Deficiency in Patients with Atypical Chest Pain in Cardiac Out Patient Department (Medical Forum Monthly, 2020)
Objective: To assess the frequency of vitamin D deficiency in patients who present with atypical chest pain in cardiac OPD.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the department of Cardialogy, Liaquat National Hospital, Karachi from Dec 2017 to June 2018.Materials and Methods: Total 305 patients of either gender with age 30 to 70 years had atypical chest pain were included in the study. Demographics and clinical history were taken from patients. Blood sample for vitamin D level was taken and sent to the institutional laboratory and results were collected to assess the outcome i-e frequency of vitamin D deficiency. The confounding variables were tested by strictly following the requirements for inclusion and exclusion.Results: There were 210 male and 95 female patients. The mean age of study subjects was 49.17±9.73 years. The vitamin D deficiency was observed in 81(26.6%) patients. The vitamin D deficiency was significantly associated with age, sun exposure, economical status, and educational status.Conclusion: Among patients with asymptomatic chest pain, high proportion of Vitamin D deficiency was observed. It was significantly associated with age, sun exposure, economical status and educational status.